5G internet of things and changing standards for computing and electronic systems - Nwajana, Augustine Onyenwe, 1979- (Advances in computer and electrical engineering (ACEE) book series., 2022)
"The emphasis of this book is on the seamless connectivity due to the development of the IoT technology and how each technology works and impacts the development of the emerging global smart city"--